STUDYING THE EFFECTS OF HEAVY METAL SALTS ON THE BLOOD PROTEINS OF AGRICULTURAL ANIMALS USING ALBUMIN PROTEIN IMITATION LABORATORY METHODS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article investigates the effects of heavy metal salts (lead, copper, zinc, mercury) on the blood plasma proteins of agricultural animals. The study analyzes how heavy metal salts form complex compounds with blood plasma proteins upon entering the organism.Biochemical and simulation statistical methods were employed to determine the binding properties of heavy metal ions to protein molecules and to elucidate their toxic mechanisms. The research findings explain the decline in quality and safety of livestock products due to heavy metal contamination. This scientific work holds significant importance in the fields of environmental protection, veterinary toxicology, and food safety.